Keunikan dan Otentisitas Pasar Ekstrim Wilken Sebagai Daya Tarik Wisata di Kota Tomohon Sulawesi Utara - Adipati, Ingryt Grity; Pitana, I Gde; Bhaskara, Gde Indra (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022, 2022)
Wilken Extreme Market is a unique and authentic traditional market in Tomohon City which sells all kinds of meats that are not normally consumed such as snake meat, forest rats, bats, cats, and dogs. This has become the center of attention for tourists to visit because the existence of this destination makes gastronomic tourism for the Minahasan people known as being the only extreme market in Indonesia that is the identity of tourism in North Sulawesi. This study uses a qualitative descriptive approach, data sources obtained through observation, interviews and documentation. The data analysis used in this study is the phenomenological method to understand what experiences are obtained and could see the final results in maintaining and developing uniqueness and authenticity, especially in trading extreme meat as a tourist attraction. The results of the study after obtaining the required data indicate the uniqueness and authenticity of the extreme market of Wilken Tomohon, that some of the meat for sale is hunted by the Minahasa community, and other types of meat are sent from different regions. called extreme markets and extreme foods. This market also has superior value for cultural, environmental and economic benefits that affect the uniqueness and authenticity of extreme markets, so that as a market traders it has its own meaning to be able to continue trading activities and focus more on market conditions, which are tourist attractions, as well as the government tourism department. , market managers, as well as travel agencies interpreting the uniqueness and authenticity of the market as local wisdom that contains elements of cultural tourism and gastronomic tourism in Extreme Markets as tourist attractions while maintaining the authenticity of the market so that it remains unique and authentic. The uniqueness and the authenticity of Wilken extreme market as a tourist attraction in Tomohon City, is expected to survive in a sustainable manner as a tourist attraction for the government and local communities. Keywords: Authenticity, cultural tourism, extreme market, gastronomic tourism, uniqueness.